Cities and the Structure of Social Interactions: Evidence from Mobile Phone Data - Konstantin Büchel; Maximilian von Ehrlich (Center for Economic Studies and ifo Institute (CESifo), 2017)
Social interactions are considered pivotal to agglomeration economies. We explore a unique dataset on mobile phone calls to examine how distance and population density shape the structure of social interactions. Exploiting an exogenous change in travel times, we show that distance is highly detrimental to interpersonal exchange. Despite distance-related costs, we find no evidence that urban residents benefit from larger networks when spatial sorting is accounted for. Higher density rather generates a more efficient network in terms of matching and clustering. These differences in network structure capitalize into land prices, corroborating the hypothesis that agglomeration economies operate via network efficiency.
Keywords: R10; R23; D83; D85; Z13; 330; social interactions; agglomeration externalities; network analysis; spatial sorting